Curly graphene nanosheets modified by nanoneedle-like manganese oxide for electrochemical capacitors. Issue 108 (20th October 2015) - Yu, Xiaoqing; Li, Kaiqi; Zhou, Haihui; Wei, Shudan; Zhang, Changjun; Li, Xueying; Kuang, Yafei
Abstract : A modified Hummers method and an aqueous solution synthesis method have been adopted to prepare curly graphene nanosheets/manganese oxide (CGN/MnO2 ) composite using multiwalled carbon nanotubes and KMnO4 as precursors in this paper. Abstract : A modified Hummers method and an aqueous solution synthesis method have been adopted to prepare curly graphene nanosheets/manganese oxide (CGN/MnO2 ) composite using multiwalled carbon nanotubes and KMnO4 as precursors in this paper. The morphologies and structure have been characterized by a range of microscopes and other techniques. MnO2 acicular crystals with about 5 nm in diameter and about 100 nm in length crisscross were uniformly dispersed on the surface of CGN to form three-dimensional nanostructured CGN/MnO2 composite. The electrochemical results show that the CGN/MnO2 composite electrode delivered a specific capacitance of 224 F g −1 at the current density of 1 A g −1 in 1 M Na2 SO4 solution, which was about 2.7 times higher than that of pure CGN (83 F g −1 ). Meanwhile, CGN/MnO2 composite exhibits high current charge–discharge capability and long-time cycling stability (the capacitance remains 95% of the initial value after 10 000 cycles). The excellent electrochemical capacitance performance of CGN/MnO2 composite was explained as follows: (1) as 10 wt% nanoneedle-like MnO2 is attached uniformly on the surface of CGN, the electronic conductivity of CGN/MnO2 composite is improved. Meanwhile, the modification of CGN by a small quantity of nanoneedle-like MnO2 further increases the interlayer distance of CGN, and the diffusivity of ions between composite electrode materials is improved as well. (2) Three-dimensional nanostructured CGN/MnO2 composite can make the full use of the double layer capacitance of CGN and the pseudocapacitive performance of MnO2 .